The Impact of the ASEAN Way and We Feeling Concepts on Indonesia's Involvement in Strengthening Regionalism - Novita H Sari; Irma Indrayani (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Indonesia is an inseparable part of a regional organization in the Southeast Asia region, namely ASEAN. The role of Indonesia also determines the movement of the ASEAN regional organization and strengthens ASEAN's position in the world view. The production of a Plan of action for the three main pillars of the ASEAN community, namely the ASEAN Security Community, the ASEAN Economic Community, and the ASEAN Socio-Cultural Community listed in the Bali Concord II which is the basis of ASEAN's future work, is one proof of Indonesia’s role in strengthening regionalism. At the time of the establishment of the ASEAN Community, it was necessary to have a sense of community among its members, so that then ASEAN organizations were required to have a sense of belonging (We Feeling) in their organization to continue to ensure the sustainability of the community in the Southeast Asia region. This paper aims to examine the contribution of interregionalism involving Indonesia as a member state of the ASEAN community in its involvement and role in strengthening regionalism through the concept of the ASEAN Way and We Feeling. This paper follows the theoretical argumentation of the concept of transactionalism, which states that intense and extensive interaction among regional actors is very important to produce a fundamental “We Feeling” foundation for the formation of regional organizations. Departing from this conception, this paper sees that the ASEAN Way factor as a universal norm of the ASEAN community provides a forum as well as boundaries for Indonesia's involvement in order to strengthen regionalism in the region. This can be seen through the non-intervention policy in the ASEAN Way, in which Indonesia is politically restricted from being involved in the internal affairs of other community members.